Analisis Dampak Kepadatan Penduduk terhadap Banjir dan Penurunan Kualitas di Bantaran Sungai Ciliwung (International Forum of Researchers and Lecturers, 2025)
Population density on the banks of the Ciliwung River, especially in the Pasar Minggu, South Jakarta, continues to experience a significant increase. This study aims to analyze the impact of population density on flood frequency and environmental degradation in the area. The method used is a mixed approach with descriptive-analytical methods, then data is collected through observation, interviews, questionnaires, and documentation. The results of the study indicate that the high population density on the banks of the river narrows the water flow and increases the volume of household waste that is directly discharged into the river, thereby exacerbating the risk of flooding and reducing the quality of water and the surrounding environment. The conclusion of this study emphasizes the importance of cooperation between the government, community, and other stakeholders in settlement planning, waste management, and environmental education and monitoring on an ongoing basis as an effort to mitigate flooding and improve the environment in the riverbank area